The Effect of Fish Meal Replacement with Golden Snail Meal on Physical Composition of Carcass and Abdominal Fat of Male Bali Ducks - S. S., Gulita; Puger, A. W.; Nuriyasa, I M. (Jurnal Peternakan Tropika; Vol 7 No 2 (2019), 2019)
This study aims to the effect of fish meal replacement with golden snail meal on physical composition of carcass and abdominal fat of male bali ducks. The design used in this study was a randomized block design (RBD) based on duck body weight totaling 20 ducks with five treatments, each treatment consisted of 4 blocks as replicates and each block consisted of one male bali duck. The treatment given is R0 (use 15% fish meal in rations as much as control), R1 (replacement of 25% fish meal with golden snail flour), R2 (replacing 50% fish meal with golden snail flour), R3 (replacement of 75% fish meal with golden snail flour), and R4 (replacing 100% fish flour with golden snail flour). The variables observed in this study included the percentage of carcass, bone, carcass fat and abdominal fat. The results of this study showed that the replacement of fish meal with golden snail flour in the ration had no effect on the percentage of meat and abdominal fat (P> 0.05) but gave effect and decreased bone percentage and increased the percentage of carcass fat (P <0.05). Based on the results of this study, it can be concluded that the replacement of fish meal in rations with golden snail flour up to 100% has the same effect on the percentage of meat and abdominal fat, replacing fish meal at the level of 50% and 100% significantly decreasing bone percentage and replacing fish meal at the level 50% significantly increases the percentage of carcass fat.   Keywords: Male Bali Ducks, Mas Snail Flour, Physical Composition of Carcasses,   Abdominal Fat